Occurrence, risks, and mitigation of antibiotic pollution in Bangladeshi aquaculture systems - Umma Salma; Anwar Hossain; Md. Shafiujjaman; Yuri Nishimura; Masahiro Tokumura; Rumi Tanoue; Tatsuya Kunisue; Kozo Watanabe; Mohammad Raknuzzaman; Kazushi Noro; Takashi Amagai; Masakazu Makino (Environmental Chemistry and Ecotoxicology)
The increasing use of antibiotics in Bangladeshi aquaculture to prevent diseases and enhance production has resulted in notable environmental contamination and resistance risks. Despite the increasing use of antibiotics in Bangladeshi aquaculture, their occurrence and the effective removal of antibiotics from aquaculture wastewater remain largely unexplored. Therefore, this study comprehensively investigated the occurrence, distribution, and ecological impacts of 26 antibiotics belongs to seven classes in the surface water of 50 aquaculture farms cultivating finfish and shellfish. Sulfadiazine, sulfamethoxazole, trimethoprim, erythromycin-H2O, and amoxicillin were the most frequently detected antibiotics, with sulfadiazine reaching a peak concentration of 25,000 ng L−1. Stripped catfish (Pangasius hypophthalmus) culture ponds exhibited the highest contamination levels, with 12 antibiotics quantified. Notably, nine of these antibiotics pose high ecological risks to sensitive aquatic organisms and are likely to exert intense selection pressure for resistance on bacterial communities. Ozonation was explored as a promising treatment method for degrading multiclass antibiotic residues in aquaculture wastewater from Bangladesh, conducted under controlled laboratory conditions in Japan. The results showed 100 % removal efficiency for sulfonamides, tetracyclines, β-lactams, and lincosamide, with fluoroquinolones achieving a 49–83 % reduction. These findings underscore the urgent need for responsible antibiotic use and effective wastewater management in Bangladeshi aquaculture. By providing novel insights into antibiotic contamination and proposing ozonation as a potentially effective treatment method, this study contributes to mitigating the environmental and public health risks associated with antibiotic pollution.